The Oxygen Generation Performance of Hollow-Structured Oxygen Candle for Refuge Space - Weixiang Wang; Longzhe Jin; Na Gao; Jianlin Wang; Mingyang Liu (Journal of Chemistry)
To improve oxygen generation performance, we dissected and analyzed the incompletely reacted oxygen candles and thus proposed the concept of the hollow-structured oxygen candle. We calculated the surface area ratio and designed the mold for hollow-structured oxygen candles at a radius of 0, 5, 9, 12, 15.5, and 20 mm. The structural stability of the oxygen candles was tested by the loading experiment. The oxygen generation rate (OGR) and other properties were explored by combustion experiments. The composition of the oxygen candles and the residual solids after combustion were observed with scanning electron microscope (SEM). The results show that, with the increase of the hollow-structure radius (r), the stability of the hollow-structured oxygen candles gradually weakens, and the oxygen candles cannot be made when r is 20 mm. The hollow structure has a positive influence on the combustion of the oxygen candles, and the extent of combustion reaction can increase to 98.3% at the most, a 28.9% increase compared with that of solid-structured oxygen candles. The analysis of the morphology of cobalt(II,III) oxide and the macroscopic and microscopic morphology of the oxygen candles before and after combustion validates the rationality of the concept of the hollow-structured oxygen candle. The best performance of the oxygen candles is obtained when r = 9 mm, where the highest extent of combustion reaction is 98.3%. The total oxygen generated is 48.75 L, and the average rate is 9.2 L/min. The test of the oxygen candles with r = 9 mm after combustion by the X-ray diffractometer (XRD) shows that these oxygen candles fully reacted. This study provides a basis for optimizing the performance of oxygen candles and for the development of the oxygen supply system fitted with the oxygen candle in spaceflight, submarine, and underground space.